Citologia oncótica e inspeção visual como métodos para triagem de lesões cervicais - Cismer, Eliana Dias Pereira (2014)
Cervical cancer (CC) is the second most common tumor in females, preceded by breast cancer. The main feature of CC is that it may be detected early. Although there are many social, economic, cultural factors and joint risks that may contribute to the development of CC factors, the most relevant risk factor is infection by human papillomavirus. Proper screening of females between 25-64 years of age may reduce the mortality rate caused by cervical cancer by up to 80 % through the diagnosis of early cancers and pre-cancerous lesions. Screening for pre-cancerous lesions is performed by tests that detect early forms of the disease, although they may also lead to some results being a false-positive or false-negative. Standard method for screening cervical lesions and cervical cancer in their early stages for the population is the Pap Smear Method (cytology or CO), one of the most effective and cost-saving public strategies. However, other techniques, such as detection of HPV DNA, visual inspection with acetic acid and Lugol, have been used successfully. Current study compared cervical cancer screening performance by users of the Brazilian Health System in Maringá PR Brazil, using the CO method, visual inspection with acetic acid (VIA) and Lugol (VILI), and colposcopy and directed biopsy as standard. The quantitative, descriptive, cross-sectional, prospective study comprised 459 females who spontaneously attended the Basic Health Units of Maringá between December 2011 and April 2012 to perform CO routine Pap. The patients were examined by CO followed by VIA and VILI. If any of the tests had any alterations, they were referred to colposcopy and biopsy, when necessary. Data were analyzed statistically. Results showed that VIA was positive in 7.8% of cases; VILI in 17.9 % and CO in 2.4 % were positive. Colposcopy was performed in 40 females of whom 7 had positive biopsies. In the case of these biopsies, 5 (71.4 %) were also positive by VIA, 4 (57.1 %) by VILI and 1 (14.3%) by CO test. Sensitivity for VIA, VILI and cytology was 71.4 %, 57.1 % and 14.3 %, respectively, whereas specificity for VIA, VILI and cytology was 90.9 %, 84.8 % and 81.8 %, respectively. The positive predictive value for VIA, VILI and CO was 61.9 %, 45.4 % and 15.7 %, respectively, while the negative predictive value was 93.6 %, 89.7 % and 81.4 %. Out of the examination types analyzed, VIA showed better sensitivity and specificity, followed by VILI. Current study indicated that the use of visual inspection tests using acetic acid and lugol plus cytology examination, especially with the activities developed in primary health care, contributed towards early diagnosis and consequently CC control. When results of favorable sensitivity and specificity for VIA and VILI and advantages such as simplicity, efficiency, low cost and especially the immediate reading of the examination result, which facilitates the processing at the first consultation, are taken into account, current investigation corroborates other tests to show that the reviewed tests were very useful for the improvement of women's health care programs, regarding the possibility of a more immediate treatment that would minimize the loss of altered cases which fail to return for follow-up and lesion treatment.